RingUpp: En videosamtalstjänst för seniorer - KALLDAL, HANNA; KARLKVIST, DANIEL; KHADEMI, THEODOR; LAM, CHARLIE; REPO WECKLAUF, ROBIN; WAHLBERG, ANDRÉ (My University, 2021)
Studies show that internet use among the Swedish population continues to grow with each year and over the last 10 years specifically, internet use in the older age groups has increased the most. In spite of this, the majority of applications today do not take seniors into consideration in the development process. This becomes a problem as aging can cause impairments of physical and cognitive ability as well as vision, making it harder to use the applications. On top of that, another problem has arisen due to the ongoing Covid-19 pandemic. As the virus is more fatal with age, it has caused an intensification of loneliness among many seniors by the means of social distancing. Therefore, it is important for elderly to stay in touch with relatives and friends, which is why a video call application adapted for seniors is relevant. This project aimed to create a video call service accommodated to the needs and abilities of seniors. A result was produced by employing an iterative design- and development process wherein a prototype of the application was built, user tested and evaluated for every iteration. Three iterations were made in total, where the third produced a software prototype. Based on the three iterations along with deeper studies on designing for seniors, a final prototype could be realized. A near complete application was developed where users could handle contacts, customize their profile and take advantage of a fully functioning video call. A positive response from user tests made it apparent that the video call application is adapted for the target audience up to a relatively suitable level. Unfortunately due to time constraints, some functionality could not be finalized. Furthermore, time constraints as well as physical constraints formed by the pandemic made it difficult to find enough testers within the target audience. Therefore, further collaboration with seniors needs to be made to ensure a more finalized service.
Keywords: seniors; elderly; video call; web development; usability; digital exclusion